1993
DOI: 10.1093/rfs/6.2.327
|View full text |Cite
|
Sign up to set email alerts
|

A Closed-Form Solution for Options with Stochastic Volatility with Applications to Bond and Currency Options

Abstract: I use a new technique to derive a closed-form solution for the price of a European call option on an asset with stochastic volatility. The model allows arbitrary correlation between volatility and spotasset returns. I introduce stochastic interest rates and show how to apply the model to bond options and foreign currency options. Simulations show that correlation between volatility and the spot asset's price is important for explaining return skewness and strike-price biases in the Black-Scholes (1973) model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
6,005
5
111

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 7,526 publications
(6,184 citation statements)
references
References 20 publications
63
6,005
5
111
Order By: Relevance
“…Similarly, a scaled increment of an integral is defined by 10) such that ∆t √ ε v → 0 + as ∆t → 0 + . An Itô-Taylor expansion to precison dt or small ∆t confirms that (6.9)-(6.10) yields the Heston [21] model, proving solution consistency. Thus, the square in (6.9) formally justifies the nonnegativity of the variance and the volatility of the Heston [21] model, for a proper computational nonnegativity-preserving procedure.…”
Section: Proper Singular Limit Formulation Suitable For Computationmentioning
confidence: 58%
See 2 more Smart Citations
“…Similarly, a scaled increment of an integral is defined by 10) such that ∆t √ ε v → 0 + as ∆t → 0 + . An Itô-Taylor expansion to precison dt or small ∆t confirms that (6.9)-(6.10) yields the Heston [21] model, proving solution consistency. Thus, the square in (6.9) formally justifies the nonnegativity of the variance and the volatility of the Heston [21] model, for a proper computational nonnegativity-preserving procedure.…”
Section: Proper Singular Limit Formulation Suitable For Computationmentioning
confidence: 58%
“…The stochastic variance is modeled with the Cox-Ingersoll-Ross (CIR) [12,13] and Heston [21] mean-reverting stochastic volatility, σ s (t) = V (t), and square-root diffusion with parameters (κ v (t), θ(t), σ v (t)):…”
Section: Optimal Portfolio Problem and Underlying Svjd Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us work in the risk neutral measure defined by the artificial currency and call S 0,i (t) the value at time t of one unit of the currency i in terms of our artificial currency (so that S 0,i can itself be thought as an exchange rate, between the artificial currency and the currency i). We model each of the S 0,i via a multi-variate Heston (1993) stochastic volatility model with d independent Cox-Ingersoll-Ross (CIR) components (Cox et al, 1985), V(t) ∈ R d . The dimension d can be chosen according to the specific problem and may reflect a PCA-type analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding dynamics of extreme events thus becomes crucial to many financial decision makings, including investment decision, hedging, policy reaction and rating. An important class of models is the continuoustime diffusions (Hull and White, 1986;Heston, 1993), which can effectively capture stochastic volatility and volatility clustering. However, empirical explorations have found that extreme events in asset prices are very unlikely to happen under standard diffusion models and a jump component is needed to capture discontinuous movements in asset prices.…”
Section: Introductionmentioning
confidence: 99%